2011
DOI: 10.1111/j.1440-1746.2010.06549.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor twenty years on: Much more than a growth factor

Abstract: Liver regeneration depends on the proliferation of mature hepatocytes. In the 1980s, the method for the cultivation of mature hepatocytes provided an opportunity for the discovery of hepatocyte growth factor (HGF) as a protein that is structurally and functionally different from other growth factors. In 1991, the scatter factor, tumor cytotoxic factor, and 3-D epithelial morphogen were identified as HGF, and Met tyrosine kinase was identified as the receptor for HGF. Thus, the connection of apparently unrelate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
399
0
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 412 publications
(411 citation statements)
references
References 73 publications
3
399
0
9
Order By: Relevance
“…As a possible reason, Met activation may require cell–cell or cell–matrix adhesions, and thus may be less efficient in poorly differentiated tumours 28. The HGF–Met system is involved in branching tubulogenesis of the lung 22 and other origins 28. In the present study, we found that the HGF–Met pathway induces HBE135 cells into a highly morphogenic, bronchioalveolar structure in 3D culture.…”
Section: Discussionmentioning
confidence: 46%
“…As a possible reason, Met activation may require cell–cell or cell–matrix adhesions, and thus may be less efficient in poorly differentiated tumours 28. The HGF–Met system is involved in branching tubulogenesis of the lung 22 and other origins 28. In the present study, we found that the HGF–Met pathway induces HBE135 cells into a highly morphogenic, bronchioalveolar structure in 3D culture.…”
Section: Discussionmentioning
confidence: 46%
“…Previous studies have demonstrated therapeutic actions of HGF in different disease models in different tissues, including the liver, kidney, lung, and nervous tissue [9,18]. Consistently, tissue-selective disruption of the Met gene in the liver, kidney, or epidermis indicated impairment in regeneration and healing and/or an increase in epithelial apoptosis [26,27].…”
Section: Discussionmentioning
confidence: 74%
“…On the basis of this biological activity, HGF and its receptor Met are involved in the development, repair, and protection of tissues [9]. Administration of HGF or expression of the HGF gene promotes tissue regeneration and improves the pathology of a variety of disease models of different tissues [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among others, the well-known receptor tyrosine kinase (RTK) signaling systems, HGF/c-Met, and EGF/EGFR (also known as ErbB1), are certainly interesting targets for experimental studies. Both signalling pathways have a remarkably pleiotropic nature and share common intracellular signalling molecules and biological effects, playing fundamental roles during development and oncogenesis [5][6][7][8]. The HGF actions, namely proliferation, survival, motility, and morphogenesis, are driven by ligand bindingdependent autophosphorylation of c-Met on specific tyrosine residues in the tyrosine kinase and C-terminal domains, followed by either adapter-mediated or direct recruitment and activation of multiple signal transducers, including Ras-ERK 1/2 mitogen activated protein kinases (MAPKs), phosphatidylinositol-3 kinase (PI3K)-AKT, phospholipase C-γ (PLC-γ), p38, and STAT3 [9].…”
Section: Introductionmentioning
confidence: 99%